End‐Truncated LAMB1 Causes a Hippocampal Memory Defect and a Leukoencephalopathy. Issue 6 (20th October 2021) - Aloui, Chaker; Hervé, Dominique; Marenne, Gaelle; Savenier, Florian; Le Guennec, Kilan; Bergametti, Francoise; Verdura, Edgard; Ludwig, Thomas E.; Lebenberg, Jessica; Jabeur, Waliyde; Morel, Hélène; Coste, Thibault; et al.
Abstract : Objective: The majority of patients with a familial cerebral small vessel disease (CSVD) referred for molecular screening do not show pathogenic variants in known genes. In this study, we aimed to identify novel CSVD causal genes. Methods: We performed a gene‐based collapsing test of rare protein‐truncating variants identified in exome data of 258 unrelated CSVD patients of an ethnically matched control cohort and of 2 publicly available large‐scale databases, gnomAD and TOPMed. Western blotting was used to investigate the functional consequences of variants. Clinical and magnetic resonance imaging features of mutated patients were characterized. Results: We showed that LAMB1 truncating variants escaping nonsense‐mediated messenger RNA decay are strongly overrepresented in CSVD patients, reaching genome‐wide significance ( p  < 5 × 10 −8 ). Using 2 antibodies recognizing the N‐ and C‐terminal parts of LAMB1, we showed that truncated forms of LAMB1 are expressed in the endogenous fibroblasts of patients and trapped in the cytosol. These variants are associated with a novel phenotype characterized by the association of a hippocampal type episodic memory defect and a diffuse vascular leukoencephalopathy. Interpretation: These findings are important for diagnosis and clinical care, to avoid unnecessary and sometimes invasive investigations, and also from a mechanistic point of view to understand the role of extracellular matrix proteins in neuronal homeostasis. ANN NEUROL 2021;90:962–975